Amorphous solid dispersion with increased gastric solubility in tandem with oral disintegrating tablets: a successful approach to improve the bioavailability of atorvastatin. (June 2015) - Salmani, Jumah Masoud M.; Lv, Huixia; Asghar, Sajid; Zhou, Jianping
Abstract Context: Serious efforts have been made to overcome the bioavailability problems of ever increasing number of poorly soluble drugs, including atorvastatin (ATO); however, enhancing its gastric solubility has not received much attention. Objectives: To improve the bioavailability of ATO by increasing its gastric solubility in a stable oral disintegration tablet (ODT) formulation. Materials and methods: Amorphous solid dispersion (ASD) of ATO with Eudragit® EPO was used as API in ODT formulation. Characterization using Differential scanning calorimetry, Powder X-ray diffraction, Fourier transform infrared drug–polymer interaction simulated by molecular modeling, solubility, dissolution and stability studies together with in vivo evaluation. Results and discussion: In ASD there was uniform distribution of drug in the polymer and it retained the amorphous nature without any chemical interactions except the possibility of hydrogen bond formation, with substantially higher gastric solubility. The dissolution profile of the ODT containing ASD was significantly improved >90% within 15 min compared with 25% of plain ATO formulation. In vivo results showed an overall enhancement in the apparent bioavailability (83% and 434% more than Lipitor® and plain amorphous ATO tablets, respectively). Combining the ASD with ODT presents a reliable solution to overcome the low solubility and bioavailability problems of ATO in a simple, robust and cost effective formulation.